Using a siphon to supply spring water to a remote village. (3rd August 2021) - Hughes, Stephen; Beard, Luke; Platten, Ben
Abstract: Siphons have been used since ancient times to transport water between two points over an intervening barrier higher than the water source. This paper describes a practical application of a siphon to provide fresh water to a remote island community in the Solomon Islands. The siphon was constructed from 25 mm diameter blue line polyethylene pipe. The vertical height difference between the water source and outflow of the siphon was estimated to be 12–18 m at the first 5000 l storage tank. The siphon filled the 5000 l tank in 5 h, corresponding to an average flow of 0.28 l s −1, close to the theoretical value obtained using the Hazen–Williams equation. This method of supplying water from hillside springs could be used in other remote rural communities around the world, especially as accessing water becomes more challenging due to climate change. The siphon principle can easily be demonstrated in the classroom with just two water containers and flexible tube.